PERAN POLA ASUH ORANGTUA DALAM PERKEMBANGAN KEMAMPUAN BICARA ANAK USIA 2-3 TAHUN - Isabella Hasiana (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2021)
The ability to speak is one of the important developments for early childhood and will help childrens’s socialization at the next stage. One of the ways to develop children’s speaking skills is the role of parenting. Each family has a diffrenet parenting pattern in educating and caring for children where it has an impact on child development. The purpose of this study is to describe the role of parenting in the development of speech abilities of children aged 2-3 years. The method used in this study uses a qualitative approach. Data collection techniques were conducted through interviews with parents and significant other as well as observing children’s speaking abilities. This research is limited to democratic and permissive parenting. The results of the study concluded that with differences in parenting patteris, it was found that there were diffrences in the development of speaking skills in early childhood. Parents with democratic parenting always communicate with their children and this makes the development of children’s speech skills more optimal. Meanwhile, permissive parents tend to let their children behave as they please and spend more time with gadgets and it also affects their speaking ability. Along with the development of this study, it was found that birth order also had an influence on the development of children’s speech abilities.